Study on the pathology and parasitic affection of liver in sheep and cattle at Mosul area - Al-Sultan, I. I.; O., Youkhana, S.; M., Mahran, O. (The Iraqi Journal of Veterinary Medicine, 1999)
A sample of (700) seven hundred out of (3000) three thousand randomly collected livers of sheep and cattle from Mosul abattoir during a biweekly visits of six months period , has been subjected to both grads and histopathological examinations. Results indicated that parasites induced the highest percen tages of tissue changes in the livers of cattle and sheep, the parasites responsible were Hydatid Cysts and Fasciola gigantica which indicated that Mosul and surrounding areas were endemic with these parasites. Typical cases of liver cirrhosis were recognized in cattle and less in sheep. Mixed infection of mentioned parasites with liver abcesses and hepatic necrosis were diagnosed more frequ ently in sheep than in cattle, a diffuse form of lesbons was round in cattle while the focal from was encountered in sheep. Congestion and degenerative changes like fatty livers were not seen in cattle but formed a respective percentage (1%) and (1.1%) in sheep. Other conditions were identified like icteric livers , than percentages were and low closely relatd in both species of animals.